A bibliometric analysis of autism spectrum disorder signaling pathways research in the past decade - Lyu, Kaifeng; Li, Jiangshan; Chen, Min; Li, Wu; Zhang, Wei; Hu, Meichao; Zhang, Yuxing; Feng, Xiang (Frontiers in Psychiatry, 2024)
This study employs bibliometric methods to comprehensively analyze Autism Spectrum Disorder (ASD) Signaling Pathways research, exploring key indicators such as nations, institutions, journals, authors, and keywords. Utilizing the WoScc database and tools like CiteSpace and VosViewer, we examined literature published between 2013 and 2023, revealing 1396 articles with a consistent increase in publications. The United States, China, and Germany lead in this field, with the University of California system and Eric Klann standing out among research institutions and Molecular Autism as a primary journal. Research themes include "elevating neuronal β-catenin levels," "Tunisian children," "Fmr1 knockout (KO) mice," "de novo mutations," "autistic children," "local translation," "propionic acid-induced mouse models," "neurosystems," "glucose metabolism," and "neuronal migration." Future research may delve into gut microbiota, genes, stress, maternal immune activation, memory, and neurodevelopmental disorders. In conclusion, our bibliometric analysis offers a comprehensive overview of ASD Signaling Pathways research, focusing on molecular mechanisms, animal models, population-based studies, and neurosystem structure and function. Future directions include exploring genes and neurodevelopmental disorders associated with ASD, investigating the gut microbiota's role, understanding the impact of stress, and exploring maternal immune activation. Additionally, in-depth research into cognitive functions, particularly memory and learning, aims to enhance individualized treatment strategies, providing new insights for future interventions and treatments.